Use of complementary and alternative medicine in head and neck cancer: Salutary or noxious - Nikunj Maniyar; Sachin C. Sarode; Shruti Thakkar; Gargi S. Sarode (Oral Oncology Reports)
Head and neck cancer (HNC) presents intricate challenges in its treatment that may result in adversative local effects impacting patient's critical functions and well-being. Alternatively, patients increasingly explore several other complementary and alternative medicine (CAM) therapies. Though clinical trials of certain CAM modalities have shown effectiveness in managing symptoms and risk behaviours allied with HNC and its treatment, evidence also suggests a need for heed. CAM usage may lead to substantial treatment delays and adverse effects with persistent concerns regarding its efficacy, safety, and potential interactions with conventional treatments, ultimately compromising therapeutic outcomes. Addressing concerns to conventional cancer care and encouraging informed decision-making are critical in ensuring comprehensive and timely interferences for HNC patients. Besides, integrating evidence-based CAM cautiously with conventional approaches holds potential for optimizing cancer management strategies.